The Implementation of the Levenberg-Marquardt for Continuous Improvement of the Management System for BPK PENABUR Education Foundation in Jakarta - H. Kusuma, Imma; Wibawa, Basuki; P. Sitepu, Bintang (International Journal of Engineering and Technology, 2018)
Improving the quality of the management system for schools that have several branches requires a big commitment from executor to managerial. By using the Levenberg-Marquardt education system concept that belongs to 15 branches, it is divided into 5 subsystems and 3 layers. The subsystems are in the form of learning dynamics, organizational transformation, human development, knowledge management and technology applications. Layer 1 is the managerial rank in each branch, the second layer is the leader as the first validator to be forwarded to the third layer, which is the head office with the final decision at the top of BPK Penabur organization. The improvement of management system starts from the gap between each subsystem that has been agreed as the standard. All components covering the secretariat (administration), Principal, Deputy Principal (student, curriculum, Facility SBI), teachers, librarians and laboratory assistants were the subjects responsible for the improvement of the management performance. While the president director and organization leader are the last layer that determines the better changes that is run. After being done gradually and continuously, the gap occurred is decreasing. By reducing the gap, the performance of the management atÂ BPK PENABUR school can become betterÂ